GJB3 promotes pancreatic cancer liver metastasis by enhancing the polarization and survival of neutrophil - Huo, Yanmiao; Zhou, Yaoqi; Zheng, Jiahao; Jin, Guangxin; Tao, Lingye; Yao, Hongfei; Zhang, Junfeng; Sun, Yongwei; Liu, Yingbin; Hu, Li-Peng (Frontiers in Immunology, 2022)
Connexins are integral membrane proteins that form channels between adjacent cells and permit the bidirectional cytosolic exchange of ions, metabolites and secondary messengers. However, its roles in pancreatic cancer metastasis remains unknown. In this study, by comparing the gene expression patterns in primary pancreatic cancer patients primary and liver metastasis specimens, we found that Gap Junction Protein Beta 3 (GJB3) significantly increased in Pancreatic ductal adenocarcinoma (PDAC) liver metastasis. Animal experiments verified that GJB3 depletion suppressed the hepatic metastasis of PDAC cancer cells. Further, GJB3 over expression increased the neutrophil infiltration. Mechanistic study revealed that GJB3 form channels between PDAC tumor cells and accumulated neutrophil, which transfer cyclic adenosine monophosphate (cAMP) from cancer to neutrophil cells, which supports the survival and polarization. Taken together, our data suggesting that GJB3 could act as a potential therapeutic target of PDAC liver metastasis.